Anti-cheating software tool: Prototype of problem generator software for linear algebra introductory test - Tuloli, M S; Latief, M; Rohandi, M (IOP conference series. Materials Science and Engineering, 2021)
To prevent students from cheating in the test, one of the strategies is by making a question that differs for each student. This approach can be used by using question-bank or question generator, the first approach is prone to cheating especially because of the widely available communication technology, this means the question generator is the only hope. This strategy is very possible to be used especially in subjects whose material has a standard pattern, such as in mathematics (calculation/structure patterns) and computer programming (logic patterns). As a branch of mathematics and also subjects in the informatics engineering curriculum, linear algebra has the potential to use this approach. But this approach involves the creation of a huge number of questions (and calculation of its answer), this requires extra efforts, we need software that can help generate questions and calculate its answers automatically. This study proposes a question-answer (problem) generation model and uses a software engineering approach (software requirement, design, implementation, and testing) to test the model. This study shows that the model implemented in this software was able to meet the need for generating questions for selected material on introductory subjects in linear algebra, with some caveat.